Evidence That a TRPA1-Mediated Murine Model of Temporomandibular Joint Pain Involves NLRP3 Inflammasome Activation - Xenia Kodji; Zizheng Kee; Robyn McKenna; Joao de Sousa Valente; Harriet Ravenscroft; Hayley McMillan; John Gamble; Yvonne Dombrowski; Paul Moynagh; David Brough; Fionnuala T. Lundy; Susan D. Brain; et al. (Pharmaceuticals, 2021)
This study investigates the role of transient receptor potential ankyrin 1 (TRPA1) in murine temporomandibular joint (TMJ) inflammatory hyperalgesia and the influence of the NLR family pyrin domain-containing 3 (NLRP3) inflammasome. Two distinct murine models of TMJ pain and inflammation (zymosan and CFA) were established. Spontaneous pain-like behaviours were observed as unilateral front paw cheek wipes. Ipsilateral cheek blood flow was used as a measure of ongoing inflammation, which, to our knowledge, is a novel approach to assessing real-time inflammation in the TMJ. Joint tissue and trigeminal ganglia were collected for ex vivo investigation. Both zymosan and CFA induced a time-dependent increase in hyperalgesia and inflammation biomarkers. Zymosan induced a significant effect after 4 h, correlating with a significantly increased IL-1β protein expression. CFA (50 µg) induced a more sustained response. The TRPA1 receptor antagonist A967079 significantly inhibited hyper-nociception. The NLRP3 inhibitor MCC950 similarly inhibited hyper-nociception, also attenuating inflammatory markers. In the trigeminal ganglia, CFA-induced CGRP expression showed trends of inhibition by A967079, whilst lba1 immunofluorescence was significantly inhibited by A967079 and MCC950, where the effect of TRPA1 inhibition lasted up to 14 days. Our results show that stimulation of TRPA1 is key to the TMJ pain. However, the inflammasome inhibitor exhibited similar properties in attenuating these pain-like behaviours, in addition to some inflammatory markers. This indicates that in addition to the therapeutic targeting of TRPA1, NLRP3 inhibition may provide a novel therapeutic strategy for TMJ inflammation and pain.